Advances in cloning functional genes for rice yield traits and molecular design breeding in China - Zhong, Qianqian; Jia, Qiwei; Yin, Wenjing; Wang, Yuexing; Rao, Yuchun; Mao, Yijian (Frontiers in Plant Science, 2023)
Rice, a principal food crop in China, significantly contributes to international food stability. Advancements in rice genome sequencing, bioinformatics, and transgenic techniques have catalyzed Chinese researchers' discovery of novel genes that control rice yield. These strides in research also encompass the analysis of genetic regulation networks and the construction of a new framework for molecular design breeding, leading to numerous transformative findings in this field. In this review, some major breakthroughs in rice yield traits and a series of achievements in molecular design breeding in China in recent years are presented, and summarizes the identification and cloning of functional genes related to yield traits and the development of molecular markers of rice functional genes, intending to play a reference role in the following molecular design breeding work and how to further improve rice yield.